Finite element analysis of cross section of TBR tire. Issue 17 (1st September 2020) - Wei, Lingjun; Liu, Haiou; Chen, HuiYan; Zhao, ZiYe
Abstract: With the development of science and technology, finite element analysis technology has gradually become the main means of radial tire analysis. However, most of the theoretical models are mainly analyzed, and there are still some differences between them and the actual tire models. In this article, the constitutive model of Yeoh rubber material is selected for the uniaxial tensile results of various rubber materials used in the tire. The material parameters are determined by the equivalent tensile strain curve of the steel cord. Taking the 12.00R20 tire as an example, with the help of ABAQUS software, a finite element method for the analysis of the tire structure is formed under the working conditions of assembly, punching gas and loading, and the necessary evaluation of the finite element results of the loading condition is also carried out. By analyzing the stress and strain of each part of the tire, the strain ratio can be used as the basis for the further analysis of thermal fatigue, and it also plays a guiding role in improving the design of tire structure.